2011
DOI: 10.1371/journal.pone.0020297
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Subtype Classification Is a Determinant of Sentinel Node Positivity in Early Breast Carcinoma

Abstract: IntroductionSeveral authors have underscored a strong relation between the molecular subtypes and the axillary status of breast cancer patients. The aim of our work was to decipher the interaction between this classification and the probability of a positive sentinel node biopsy.Materials and MethodsOur dataset consisted of a total number of 2654 early-stage breast cancer patients. Patients treated at first by conservative breast surgery plus sentinel node biopsies were selected. A multivariate logistic regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
81
2
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(97 citation statements)
references
References 29 publications
12
81
2
2
Order By: Relevance
“…These findings were in accordance with previous reports [7][8][9][10][11][12][13]. Our study could not find out the association between molecular subtype and SLN metastasis, in contrast with previous reports [3,6,[14][15][16][17][18][19][20][21][22]. Possible explanation to the discrepancy between previous reports and our results is that the distribution in among subtype might affect the results: HER 2 type was very few (7.0%), and this seems to be the reason why low frequency of SLN metastasis in HER 2 subtype was shown in our study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These findings were in accordance with previous reports [7][8][9][10][11][12][13]. Our study could not find out the association between molecular subtype and SLN metastasis, in contrast with previous reports [3,6,[14][15][16][17][18][19][20][21][22]. Possible explanation to the discrepancy between previous reports and our results is that the distribution in among subtype might affect the results: HER 2 type was very few (7.0%), and this seems to be the reason why low frequency of SLN metastasis in HER 2 subtype was shown in our study.…”
Section: Discussionsupporting
confidence: 86%
“…A various clinicopathological factors have been identified as independent predictors of axillary lymph node metastasis in early stage breast cancer [6]. These include clinical palpability [7][8][9][10], tumor size [7][8][9][10][11][12][13], lymphatic or vascular involvement [7][8][9][10][11]13], tumor grade [7,10], hormone receptor (HR) status [12,13], age [8,11,12], and molecular subtypes [3,6,[14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of lymph node lesions increased in cases of cancers exhibiting HER2 overexpression [27,30]. However, it was notably lower among patients with luminal A type of cancer and triple negative tumors [31,32] (in our study this proportion was 26.4% and 32.2%, respectively).…”
Section: Discussioncontrasting
confidence: 54%
“…Due to a high proportion of lymph node metastases noted among patients with luminal B1 and HER2-positive cancers (exceeding 50% of the total number of cases -vs 38.6% and 42.1%, respectively, in our material), Reyal et al suggested the need for consideration of SLNB in these groups of patients [30]. However, possible changes in patient qualification for this type of procedure proposed by the authors have not been widely accepted.…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, several studies have suggested that the triplenegative tumor subtype may predict a lower risk of nodal involvement. [35][36][37][38][39] Because biology and systemic therapy influence the natural evolution of disease, the indications for axillary surgery should take these factors into consideration. Single-center studies do not demonstrate any benefits in performing axillary surgery, but meta-analyses lead to a different conclusion.…”
Section: Author's Personal Copymentioning
confidence: 99%